Free Amino-acid Concentrations in Fetal Fluids. Issue 5725 (26th September 1970) - Cockburn, F.; Robins, S. P.; Forfar, J. O.
Abstract : The pattern of free amino-acid concentrations in maternal venous plasma, fetal umbilical arterial plasma, fetal urine, and amniotic fluid at 15 to 20 weeks' gestation has been determined. Free amino-acid concentrations were greater in fetal plasma than in maternal plasma, amniotic fluid, or fetal urine. The ratios of amino-acid concentrations in fetal umbilical arterial plasma and urine indicate that the fetal kidney can effectively conserve amino-acids, possibly reaching an adult level of competence in this respect. There was little correlation between amino-acid concentrations in the fluids analysed with the exception of that between amniotic fluid and fetal urine.